Internalisasi Nilai Moderasi Beragama di Sekolah Melalui Ekskul Rohis - Werdiningsih, Wilis; Umah, Restu Yulia Hidayatul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
Currently, Islamic moderation (wasathiyyah) is emphasized as the mainstream of Islam in Indonesia. This mainstreaming idea is the answer to the emergence of various problems in the name of religion. The difference in diversity in Indonesia, including in terms of religion, is something that cannot be denied. Therefore, tolerance in the midst of differences that exist in society is an important thing to understand and do together. Education in schools is one means of instilling the values of religious moderation in students. Not only in classroom learning, but this moderation value can also be instilled through extracurricular activities. Rohis is extracurricular that focuses on religious development. This study uses a library research approach. The results show that values in religious moderation can be instilled through various activities in extracurricular Rohis. The coaches and mentors of the Rohis need to plan for the activities of the Rohis by inserting the values of religious moderation. As well as providing special assistance to students so that they have a deep understanding related to religious moderation.